Environmental assessment of the Tung cultivation through life cycle analysis - Bernál, Marcelo; Schneider, Rosana; Machado, Ênio (International Journal of Engineering and Technology, 2014)
Over the past few decades, conventional agriculture has been facing serious crises caused by numerous factors, including poor soil management and the excessive application of pesticides. Thus, alternative production systems have been developed, including agroforestry systems, especially those that produce both energy and food. The objective of this study was to environmentally evaluate the culture of Aleurites fordii Hemls. (Tung) using the Life Cycle Assessment method with the SimaPro 7.3.2 software. The results revealed that in family farms that use less mechanization to harvest crops, the primary category of environmental impact was land use, which included the removal of animal and vegetable species and ecosystem changes. The full impact of this category was 1741.21 m2yr PDF (potentially disappeared fraction). Subsequently, prognostics were established for the reduction of such impacts, and we conclude that Tung has a high potential for agricultural installation with high responsibility to the environment. Keywords: Environmental factors, Aleurites fordii Hemls, Life Cycle Management, Tung.